Design of a new pneumatic impact actuator of a Split Hopkinson Pressure Bar (SHPB) setup for tensile and compression testing of structural adhesives. (May 2021) - Tenreiro, A. Francisco G.; Silva, Carlos M.; Lopes, António M.; Nunes, Paulo D.P.; Carbas, Ricardo J.C.; da Silva, Lucas F.M.
Highlights: New architecture for impact testing apparatus, the Split Hopkinson Pressure Bar. New pneumatic actuator architecture that can reach high speeds. Functional modelling of the pneumatic actuator. Abstract: Adhesive joining became a common manufacturing technique for joining materials, particularly in the automobile and aerospace industries. However, only recently the scientific community started to study the mechanical behavior of bonded joints, having in mind impacts and high strain-rate solicitations. As such, a new architecture for a Split Hopkinson Pressure Bar (SHPB) test machine is proposed to test adhesive bulk, as well as, Mode I, Mode II and Mixed-Mode adhesive joint specimina. This paper presents a novel pneumatic actuation system for the SHPB machine, able to reach velocities of roughly 25 m s − 1 (or 90 km h − 1 ). These velocity requirements are deduced from mathematical models describing the behavior of the specimina under SHPB testing. The actuator dynamics is assessed by means of a functional numerical simulation, involving the mechanical and fluid dynamics. The model includes details such as the reservoir and pneumatic valves, thermodynamic behavior of the pneumatic chambers, and the air leakage due to the absence of physical contact between the static and moving components. Additionally, the mechanical design of the non-conventional actuator is discussed, highlighting construction details.